BI-RADS® 3 lesions at contrast-enhanced breast MRI: is an initial short-interval follow-up necessary?. (April 2014) - Bahrs, Sonja D; Baur, Astrid; Hattermann, Valerie; Hahn, Markus; Vogel, Ulrich; Claussen, Claus D; Siegmann-Luz, Katja C
Background: Magnetic resonance imaging (MRI) BI-RADS® 3 lesions should have a very high probability of being benign. To prove benignity most institutions do follow-up MRI. Purpose: To evaluate the necessity of initial short-interval follow-up after 6 months as it is suggested for mammographic BI-RADS®3 lesions. Material and Methods: We analyzed 163 consecutive MRI-BI-RADS® 3 lesions on follow-up MRI: 75 masses (46%), 67 foci (41.1%), and 21 (12.9%) non-mass-like enhancing lesions (NMLE). Results: During MRI follow-up (mean time, 563 days) 20% of the lesions disappeared, 23% decreased, 52% did not change, and 4.9% showed increase. All increasing lesions were biopsied (5 benign, 2 ductal carcinoma in situ, 1 invasive carcinoma). The rate of malignancy was 1.8%. All malignant lesions (1 mass, 1 focus, 1 NMLE) showed increase at initial follow-up after a mean interval of 190 days. Conclusion: In this study the malignancy rate of MRI-BI-RADS® 3 lesions corresponded to mammographic BI-RADS® 3 lesions. Initial short-interval MRI should be suggested to identify malignant MRI-BI-RADS® 3 lesions.